Gestión financiera y la toma de decisiones en la cooperativa Juan Pío de Mora Ltda., en la ciudad de Guaranda - Trujillo Trujillo, Luis Alberto (2024)
The role of financial management and decision making in the Juan Pío de Mora Savings and Credit Cooperative Ltda. of the city of Guaranda is not just significant, but crucial. These two variables are intricately linked, with each influencing the other. Understanding and mastering these variables is paramount for the Cooperative's smooth operation. In this research work, both general and specific objectives and hypotheses were proposed. These contribute to the theoretical framework where the study variables are described, providing sufficient knowledge to build a comprehensive scorecard that can be practically applied when making decisions within the Cooperative. A hypothetical-deductive methodology was used with the purpose of stating and verifying the hypothesis. This method was based on the collection of statistical data to proceed with its analysis, facilitating the study of the research phenomenon and providing a thorough solution to the problem posed in the research work. As collection techniques, interviews with the cooperative manager and the survey of its workers were used, allowing us to learn its shortcomings and virtues. The results show low communication within the collaborative, for which a solution has been found with the balanced scorecard proposal.